2022
DOI: 10.1093/asj/sjac082
|View full text |Cite
|
Sign up to set email alerts
|

Practice Advisory on Gluteal Fat Grafting

Abstract: On January 31, 2018, The Multi-Society Task Force for Safety in Gluteal Fat Grafting released a Practice Advisory regarding gluteal fat grafting. The Task Force was assembled in the wake of several highly publicized patient deaths involving Brazilian Butt Lift ("BBL”) and produced a second practice advisory in August 2019. In 2021 the ASAPS President commissioned a Working Group on BBL Patient Safety, charging the Group to address new guidelines affecting safety and welfare of BBL patients. The “Practice Advis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…24,25 In addition, the newest recommendations for gluteal adipose grafting (after the 2018 practice advisory from the Multi-Society Task Force for Safety in Gluteal Fat Grafting) include the use of ultrasoundguided documentation of cannula placement before and during fat injection and the limitation of three BBL cases as a maximum amount of total operative cases per day. 26 To our knowledge, there has not been any fatality or pulmonary fat embolism reported in the medical literature after IM fat grafting in a muscle other than the gluteus major, [27][28][29][30][31] or any case report of ACS following aesthetic procedures of the lower limb. [32][33][34] Animal studies have shown that IM fat grafts have no association with long-/ short-term events of fat embolism after autologous fat transplantation, which further supports the special case of the gluteus major muscle.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In addition, the newest recommendations for gluteal adipose grafting (after the 2018 practice advisory from the Multi-Society Task Force for Safety in Gluteal Fat Grafting) include the use of ultrasoundguided documentation of cannula placement before and during fat injection and the limitation of three BBL cases as a maximum amount of total operative cases per day. 26 To our knowledge, there has not been any fatality or pulmonary fat embolism reported in the medical literature after IM fat grafting in a muscle other than the gluteus major, [27][28][29][30][31] or any case report of ACS following aesthetic procedures of the lower limb. [32][33][34] Animal studies have shown that IM fat grafts have no association with long-/ short-term events of fat embolism after autologous fat transplantation, which further supports the special case of the gluteus major muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Preferring the desired fat size will not only create the desired result, but also allow for regeneration in the superficial area. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Preferring the desired fat size will not only create the desired result, but also allow for regeneration in the superficial area. 16 In order for the fat graft to be successful in radiation injury and burn reconstruction, two basic problems must be solved. These are high pressure and vascular insufficiency.…”
Section: Meaningmentioning
confidence: 99%
“…The procedure has been made even safer with the advent of handheld high-definition ultrasound, which gives a visual on the anatomical location, and depth of the transferred fat into the buttocks, thus avoiding the gluteal muscles and reducing risks of embolus and vascular origin complications [38][39][40][41].…”
Section: Gluteal Contouringmentioning
confidence: 99%